Early life growth and developmental trajectory in children with biliary atresia undergoing primary liver transplantation - Fang, Heping; Li, Zehao; Xian, Ruoling; Yin, Yu; Wang, Juan; Guo, Hongling; Dai, Xiaoke; Zhang, Mingman; Hu, Yan; Li, Yingcun (Frontiers in Pediatrics, 2023)
Objective: To clarify the early growth and developmental characteristics of children with biliary atresia (BA) undergoing primary liver transplantation (pLT). Methods: A prospective cohort study, which specifically focused on BA-pLT children, was conducted after the diagnosis of BA by following the children at the time of pLT and 1, 3, 5, 7 months and 1 year after pLT for growth and developmental monitoring. The growth parameters were calculated according to the WHO standard, and the developmental status was assessed using Denver Developmental Screening Tests. Results: A total of 48 BA children who received pLT at the age of 5.00 ± 0.94 months were analyzed. The weight-for-age Z value (ZW) and length-for-age Z value (ZL) were higher than the head circumference-for-age Z value (ZHC) at pLT (P=0.002 and 0.02), but they were all lower than the WHO growth standard (Z=0) (P<0.001). The ZW and ZHC decreased first and then returned to the population level at 1 year after pLT, while the ZL only returned to the preoperative status and was lower than the ZW and ZHC (P<0.001). Developmental screening showed that 35% (17/48) of the children were suspicious and 15% (7/48) were abnormal at 1 to 4 months after pLT, the most likely time to be suspected of developmental delay. At 1 year after pLT, gross motor skill delay still existed (12/45, 27%), and language skill delay began to appear (4/45, 9%). Conclusions: BA-pLT children suffer from growth and developmental problems. Low ZHC is the main growth problem before pLT, while low ZL is the problem after pLT. Developmental delays are significant after pLT, especially in motor and language skills. The current study suggested that further studies are warranted to clarify the long-term growth and developmental outcomes of BA-pLT children, to compare them with children undergoing the Kasai procedure and to explore their influencing factors and possible mechanisms.